Coumarin carbonic anhydrase inhibitors from natural sources - Claudiu T. Supuran (Taylor & Francis Group, 2020)
Coumarins constitute a relatively new class of inhibitors of the zinc enzyme carbonic anhydrase (CA, EC 4.2.1.1), possessing a unique inhibition mechanism, acting as "prodrug inhibitors." They undergo the hydrolysis of the lactone ring mediated by the esterase activity of CA. The formed 2-hydroxy-cinnamic acids thereafter bind within a very particular part of the enzyme active site, at its entrance, where a high variability of amino acid residues among the different mammalian CA isoforms is present, and where other inhibitors classes were not seen bound earlier. This explains why coumarins are among the most isoform-selective CA inhibitors known to date among the many chemotypes endowed with such biological activity. As coumarins are widespread secondary metabolites in some bacteria, plants, fungi, and ascidians, many such compounds from various natural sources have been investigated for their CA inhibitory properties and for possible biomedical applications, mainly as anticancer agents targeting hypoxic tumours.